Searching for >177 TeV Gamma Rays in the Vicinity of Mrk 501 with HAWC - Albert, Andrea; Abeysekara, A. U.; Alfaro, R.; Alvarez, C.; Álvarez, J. D.; Angeles Camacho, J. R.; Arteaga-Velázquez, J. C.; Arunbabu, K. P.; Avila Rojas, D.; Ayala Solares, H. A.; Babu, R.; Baghmanyan, V.; et al. (Proceedings of Science, 2022)
HAWC has recently developed 2 new analysis techniques that reconstructs the energy of each gamma-ray event. With this new analysis HAWC has detected several Galactic sources with emission above 100 TeV. Additionally the HAWC Collaboration has developed new event reconstruction algorithms called “Pass 5”. Using the energy estimators and Pass 5 we search for >177 TeV emission in the vicinity of Mrk 501. High-energy emission from Mrk 501 could, for example, be evidence of Axion Like Particles, a theoretical dark matter candidate. We find a hint of a high-energy lobe within 0.5◦ of Mrk 501 using both energy estimators.
CRIS-Team Scopus Importer:2022-12-23